The Concept of Violence in Buddhism - Winja Kumari; Junaidi Junaidi; Haudi Haudi; Lisniasari Lisniasari; Eko Pramono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This paper came up to the surface of ethical confusion of why people tend to use violence to solve many problems. The method used in writing this article is library research. In this article, the author collects data from suttas, articles or journals related to the study of violence in Buddhism. The author analyzes this topic concerning violence in the perspectives of Buddhism generally, especially advices and stories that had been recorded in the Pali Canon and other sources. For the Examples are from the story of Angulimala, the dispute over water between the Sakyas and the Koliyas. In human relationships, it is impossible to avoid disagreement. People might have similar or totally opposite views. The disagreement can be solved by loving speech, deep listening, and understanding. It is not always the case that all disagreement can be solved. If the disagreement prolongs for a certain period of time, then disputes start to arise. People tend to be attached to their own view or collective view. For the next unpredictable phase, they may be using violence of body, speech, and mind to persuade other people. Violence pertained to the use of physical, speech, and ill will to harm others is to inflict fear. Human long history related closely to fear when making a decision, so no wonder inflicting fear can be one of the ways. Buddhism is a peaceful religion. This is a religion that is no violence in it. There is a key virtue of Buddhism that is the virtue of No violence. No violence refers to the action of non-harming, not to injure, or non-violence. It applies to all living beings. The teaching of the Buddha is clearly associated with non-violence or the principle of Ahimsa (non violence), therefore inflicting fear is inconsistent with the Ahimsa (non violence) which’s teaching of the Buddha.